THE ROLE OF INSULIN RESISTANCE IN THE DEVELOPMENT OF ENDOMETRIAL HYPERPLASIA IN PREMENOPAUSAL WOMEN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Endometrial hyperplasia in women of premenopausal age represents an important problem in gynecology because of its relatively high occurrence and the possibility of progression to malignant disease. Metabolic syndrome and excessive body weight are considered major contributing factors that increase the likelihood of abnormal proliferative processes in the endometrium. These conditions are frequently associated with menstrual irregularities, infertility, and an early onset of menarche. In a clinical observation involving 42 patients, mild obesity was identified in 40% of cases, moderate obesity in 35%, and severe obesity in 15% of the examined women. The obtained data suggest a significant association between metabolic disorders and the development of endometrial hyperplasia in the premenopausal period, underlining the importance of careful medical supervision and timely evaluation of women who present with metabolic risk factors.